Community-Based Study on the Misuse of Antibiotics in Paediatrics Otolaryngic Infections in Kirkuk - Tunjai Namiq Faiq; Ozdan Akram Ghareeb (Genius Journals, 2023)
Antibiotics are the treatment of choice for many bacterial infections, but the increasing misuse of antibiotics has led to a growing emergence of antimicrobial resistance. This study aimed to appreciate current trends in misuse or inappropriate prescribing of antibiotics in the management of pediatric otolaryngic infections. This community-based descriptive study was conducted in the center of Kirkuk Governorate (Iraq) between November 2021 and March 2022. The use of 300 prescriptions for otolaryngic infections in children was evaluated, by recording data related to infections as well as the appropriateness of the antibiotics, to determine if the antibiotic prescriptions used are appropriate or not. The results showed that out of 300 prescriptions, 210 (70%) had viral infections vs. 90 (30%) non-viral, including bacterial infections, and (90%) of these viral infections had antibiotics misuses. The responsibility for this misuse of antibiotics was recorded among parents with the highest rate (40%) then general practitioner physicians (25%). Also, it was noted that (80%) of the inappropriate prescriptions were orally treated. The study concluded that the proportions of antibiotics misuses of otolaryngic infections were high, so it recommended adherence to instructions for prescribing antibiotics, and activating educational and awareness programs that reduce inappropriate prescriptions, especially for general practitioner physicians. Also, the emphasis on following up pharmacies periodically to prevent the dispensing of antibiotics without medical prescriptions
Keywords: Otolaryngic infections; antibiotic prescriptions; viral infections